STUDI PEMANFAATAN LIMBAH MINYAK JELANTAH SEBAGAI REJUVENATOR PADA CAMPURAN RAP - Sepriyanna, Irma; Putranto, Leksmono S; Subagio, Bambang Sugeng; Najid, Najid (Politeknik Negeri Jakarta, 2025)
The increasing demand for pavement materials necessitates more sustainable solutions, one of which is the utilization of Reclaimed Asphalt Pavement (RAP) containing aged asphalt from recycled layers. However, the high incorporation of RAP often faces challenges such as increased stiffness, reduced ductility, and degradation of viscoelastic properties due to aging. In this context, waste cooking oil (WCO) has attracted significant attention as an eco-friendly and cost-effective rejuvenator. This study presents a systematic literature review on the application of WCO in RAP mixtures, focusing on its chemical characteristics, effects on rheological and mechanical properties, implementation challenges, and performance enhancement strategies through chemical modification and additive incorporation. The findings indicate that WCO effectively reduces binder viscosity, improves flexibility, enhances low-temperature cracking resistance, and extends the fatigue life of RAP mixtures. However, excessive WCO content may reduce Marshall stability and rutting resistance. Synergistic approaches such as polymer addition, nano-material incorporation, or chemical pre-treatment have proven effective in addressing these limitations. This review highlights WCO’s potential as a sustainable rejuvenator while emphasizing the need for further research on dosage optimization, quality standardization, and long-term performance evaluation to support large-scale industrial implementation.